2013
DOI: 10.1128/aac.00923-13
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Ceftaroline against Enterococcus faecium PBP5

Abstract: The opportunistic human pathogen Enterococcus faecium overproduces the low-affinity PBP5. In clinical strains, mutations in PBP5 further reduce its acylation rate by ␤-lactams. Previous studies have reported that ceftaroline had poor inhibitory activity against ␤-lactam-resistant E. faecium strains. In this study, we show that ceftaroline exhibits killing activity against our laboratory-derived ampicillin-resistant E. faecium mutant that overproduces a wild-type PBP5 and that ceftaroline inactivates PBP5 much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
1
11
0
1
Order By: Relevance
“…Recent data have also demonstrated that ceftobiprole is synergistic with DAP against VRE that are both DAP susceptible and DAP nonsusceptible (44). Previous work has demonstrated that ceftobiprole possesses activity against enterococcal PBP5 and PBPs 1 to 4 similar to, although not quite as potent as, that of CPT (40). These data further suggest the importance of PBP binding for synergistic DAP activity against enterococci.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Recent data have also demonstrated that ceftobiprole is synergistic with DAP against VRE that are both DAP susceptible and DAP nonsusceptible (44). Previous work has demonstrated that ceftobiprole possesses activity against enterococcal PBP5 and PBPs 1 to 4 similar to, although not quite as potent as, that of CPT (40). These data further suggest the importance of PBP binding for synergistic DAP activity against enterococci.…”
Section: Discussionsupporting
confidence: 54%
“…In that study, the DAP-CRO combination was evaluated against E. faecium 8019, and the activity of that combination was similar to the activity we observed against 8019 with the DAP-CPT, DAP-ERT, and DAP-AMP combinations. CRO, however, possesses a narrower PBP binding profile than CPT (40). Based on the available data, it appears that there is an important combination of PBPs that should be bound for optimal DAP activity, and further study is needed to evaluate the optimal PBP binding profile for DAP enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MICs of 1 and 2 mg/l, respectively. At 6 mg/kg, 9 of 11 (82%) and 11 of 12 (91%) culture-negative vegetations in rats infected with VanA and VanB type, respectively Levine et al (2007) [119] and ceftaroline were only effective for E. faecalis, but recent data insist that the former has in vitro activity against E. faecium with lowaffinity PBP 5, which confers a β-lactamase phenotype [190] and recent evidence showed that ceftaroline inactivates PBP5 even faster than ceftobiprole [191]. Besides, there are experimental data showing that the combination of beta-lactams (ceftaroline, ertapenem, ampicillin) with daptomycin is synergistic [192,193] and restores daptomycin activity in daptomycinnonsusceptible strains [194].…”
Section: Sierrahoffman Et Almentioning
confidence: 95%
“…Similarly to other β-lactam antibacterial agents, ceftobiprole exerts its antibacterial activity by binding to important penicillin-binding proteins (PBPs) and inhibiting their transpeptidase activity (12), which is essential for the synthesis of the peptidoglycan layer of bacterial cell walls. Ceftobiprole binds to multiple PBPs in clinically relevant pathogens, which provides its broad activity spectrum (4,5,7,12,13). The anti-MRSA activity of ceftobiprole is attributed to its rapid and tight binding to the mutant PBP2a form (encoded by the mecA gene) that is able to confer resistance to methicillin and most β-lactam antibiotics (12).…”
Section: Introductionmentioning
confidence: 99%